Economic development what everyone needs to know - Giugale, Marcelo M. (Oxford Oxford University Press, 2014)
"The practice of economic development has undergone significant transformation over the past decade, due to globalization and democratization. While beneficiaries previously held little sway in the way international economic institutions delegated funds for projects, today it would be difficult-if not impossible-for the average government or for the average multilateral organization to build a road, reform an education curriculum, or sign a mining concession without, at a minimum, a process of consultation with those affected. This change has created a greater demand for development knowledge. Economic Development: What Everyone Needs to Know provides a clear and concise introduction to the development problems that policy-makers, professionals, development agencies, NGOs, charities, and private citizens face. Beginning with the basic concepts that inform the practice of development, this wide-ranging book addresses the major challenges that shape the field, highlighting the doubts, trade-offs, and dilemmas. Drawing on his more than twenty-five years of experience working in development in the Middle East, Eastern Europe, Central Asia, Latin America and Africa, Marcelo Giugale illustrates his chapters with real-life examples from all over the globe. He looks at a host of topics including the reasons why seemingly obvious reforms never happen, power dynamics between governments and beneficiaries, government corruption, state violence, natural resources, globalization and trade, anticipating global crises, measuring equity, ending poverty, the "new" poor, gender, indigenous peoples, children, health care, food prices, and technology. While development is a complex area in which there are no definitive answers, Giugale highlights the very real challenges that face the profession now and will continue to face development practitioners in the years to come"--Provided by publisher.
"This book brings non-expert readers to the frontier of economic development. How governments actually function, the basics of economic policy, new tools for social assistance, the reality of Africa, and the challenges of inclusion, education, health, infrastructure, data, foreign aid, among others, are explained through simple, jargon-free questions and answers"--Provided by publisher.
Introduction -- Part I - Governments: One Day, They Will Work For You -- 1. Why Do Obvious Reforms Never Happen? The Political Economy of Things -- 2. How Will I Relate To My Government? The State and Me -- 3. Do We Really Care About Graft? Cairo, Corruption and Cultural Change -- 4. Why Can't We Stop Conflict? Violence and the Failure of Institutions -- 5. Are Natural Resources A Good Thing? Blessed by Nature, Cursed By Politics -- Part II - Economic Policy: The Basics You've Got to Get Right -- 6. Has Economic Wisdom Changed? Macroeconomics Catches Up With Reality -- 7. A New, Wasted Bonanza? Commodities and that Uncomfortable Feeling of Wealth -- 8. Will Globalization End? A Different Kind of Trade -- 9. Why Is It So Difficult to Agree on Tax Reform? -- 10. How Do You Prepare For Another Global Crisis? -- Part III - Social Policy: Old War, New Weapons -- 11. How Do We Help Now? The Lingering Global Crisis And The New Poor -- 12. Can We End Poverty? -- 13. Is There A Way To Measure Equity? The Human Opportunity Index -- 14. Why Are Statistics So Important? Poverty in the Era of Data -- 15. Who Really Benefits? Winners, Losers and The Beauty of Impact Analysis -- Part IV - Inclusion: Those Who Are Always Left Behind -- 16. Will We Ever Live In Gender Parity? Women, Growth and Generational Change -- 17. Has Globalization Helped or Hurt Women? -- 18. Are Average Housewives Powerless? The Greatest Generation of Argentine Women -- 19. What Have Economists Learned About Indigenous Peoples? -- 20. Why Is Early Childhood Development So Difficult? The Child From Mozambique -- Part V - Sectors: What Ministers Will Worry About-or Should -- 21. How Will Technology Shape The World of Tomorrow's Leaders? -- 22. How Will Tomorrow's Infrastructure Be Built? -- 23. Can Emerging Economies Have Universal Health Coverage? -- 24. Is There New Power In Entertainment Education? -- 25. How Do You Deal With Rising Food Prices? -- Part VI - Africa: The Last Frontier -- 26. Is Africa's Emergence For Real? -- 27. Can Africa Be Defragmented? -- 28. Who Will Be Africa's Brazil? -- 29. Is There A Latin Solution to Africa's Problem? -- 30. How Have The World's Newest Nations Fared? -- 31. Can Africa Compete With China? -- 32. Can Africa Feed Africa? -- Glossary -- Suggested Further Reading -- Index.
Includes bibliographical references (pages 135-145) and index.
Keywords: Economic development; Economic policy; Social policy; Globalization -- Social aspects